BRAT1 mutations present with a spectrum of clinical severity. Issue 9 (9th June 2016) - Srivastava, Siddharth; Olson, Heather E.; Cohen, Julie S.; Gubbels, Cynthia S.; Lincoln, Sharyn; Davis, Brigette Tippin; Shahmirzadi, Layla; Gupta, Siddharth; Picker, Jonathan; Yu, Timothy W.; Miller, David T.; Soul, Janet S.; et al.
Abstract : Mutations in BRAT1, encoding BRCA1‐associated ATM activator 1, are associated with a severe phenotype known as rigidity and multifocal seizure syndrome, lethal neonatal (RMFSL; OMIM # 614498), characterized by intractable seizures, hypertonia, autonomic instability, and early death. We expand the phenotypic spectrum of BRAT1 related disorders by reporting on four individuals with various BRAT1 mutations resulting in clinical severity that is either mild or moderate compared to the severe phenotype seen in RMFSL. Representing mild severity are three individuals (Patients 1–3), who are girls (including two sisters, Patients 1–2) between 4 and 10 years old, with subtle dysmorphisms, intellectual disability, ataxia or dyspraxia, and cerebellar atrophy on brain MRI; additionally, Patient 3 has well‐controlled epilepsy and microcephaly. Representing moderate severity is a 15‐month‐old boy (Patient 4) with severe global developmental delay, refractory epilepsy, microcephaly, spasticity, hyperkinetic movements, dysautonomia, and chronic lung disease. In contrast to RMFSL, his seizure onset occurred later at 4 months of age, and he is still alive. All four of the individuals have compound heterozygous BRAT1 mutations discovered via whole exome sequencing: c.638dupA (p.Val214Glyfs*189); c.803+1G>C (splice site mutation) in Patients 1–2; c.638dupA (p.Val214Glyfs*189); c.419T>C (p.Leu140Pro) in Patient 3; and c.171delG (p.Glu57Aspfs*7); c.419T>C (p.Leu140Pro) in Patient 4. Only the c.638dupA (p.Val214Glyfs*189) mutation has been previously reported in association with RMFSL. These patients illustrate that, compared with RMFSL, BRAT1 mutations can result in both moderately severe presentations evident by later‐onset epilepsy and survival past infancy, as well as milder presentations that include intellectual disability, ataxia/dyspraxia, and cerebellar atrophy. © 2016 Wiley Periodicals, Inc.